The Role of Vitamin A in Patients with Cystic Fibrosis - N.V. Rogovyk; L.Y. Bober (Zaslavsky O.Yu., 2013)
Cystic fibrosis is hereditary monogenic exocrine disease, which manifests itself most often by disorders in bronchopulmonary and digestive systems. The affection of the latter leads to deficiency of liposoluble vitamins A, D, E and K in the body of the patient. The lack and excess of vitamin A in this disease may contribute to a number of pathological states and aggravate the disease. Therefore, in the records of all European centers of cystic fibrosis it is recommended to carry out annual determination of the levels of vitamin A, followed by individual dose adjustment.